IMPLEMENTING COMPUTER ASSISTED LANGUAGE LEARNING FOR SPEAKING CLASS - Puspita Mayaratri (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Computer Assisted Language Learning (CALL) is a program derived from CAL (Computer-Assisted Learning) which is implemented to language and the prime focus of CALL is on the usage of computers in language learning. Much of the research has been aimed at improving written communication skills and little has been done to address the issue of increasing oral proficiency. In second/foreign language classrooms, the CALL environment creates situations that stimulate interest, allows dialogue and communication, enhances creativity, fosters a sense of personal worth, facilitates collaboration among students working together, permits rich learning experiences for all students, and strengthens communication skills. By using CALL, many resources of material can be easily developed in teaching learning process.